2017
DOI: 10.1007/s13300-017-0339-3
|View full text |Cite
|
Sign up to set email alerts
|

Skin Autofluorescence is a Noninvasive Surrogate Marker for Diabetic Microvascular Complications and Carotid Intima–Media Thickness in Japanese Patients with Type 2 Diabetes: A Cross-sectional Study

Abstract: IntroductionAdvanced glycation end-products (AGEs) are known to play an important role in the pathogenesis of diabetic complications. Skin autofluorescence (AF), a marker of AGE accumulation in tissue, can be measured noninvasively using a skin AF reader. The present study aimed to evaluate the relationships of skin AF with diabetic microvascular complications and carotid intima–media thickness (IMT), a surrogate marker for atherosclerosis, in Japanese subjects with type 2 diabetes (T2D).MethodsOne hundred six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…The present study also confirmed that skin AF was associated with arterial thickening assessed by max-IMT and arterial stiffness assessed by baPWV, which was consistent with previous studies 7 9 , 21 ) . Considering the crucial roles of AGEs in the pathogenesis of atherosclerosis, it is reasonable that the index of AGEs accumulation in skin is associated with arterial thickening and/or stiffness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study also confirmed that skin AF was associated with arterial thickening assessed by max-IMT and arterial stiffness assessed by baPWV, which was consistent with previous studies 7 9 , 21 ) . Considering the crucial roles of AGEs in the pathogenesis of atherosclerosis, it is reasonable that the index of AGEs accumulation in skin is associated with arterial thickening and/or stiffness.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, the level of accumulated fluorescent AGEs in the skin has become measurable non-invasively as skin autofluorescence (skin AF) using an autofluorescence reader. Skin AF intensity is correlated with accumulation of skin AGEs assessed by skin biopsy 5 ) and has been shown to be associated with coronary artery calcification score used for the predictor of CVD 6 ) , diabetic complications and above mentioned indices of early-stage atherosclerosis such as carotid IMT and PWV 7 9 ) . With regard to endothelial dysfunction, however, such an association has not yet been validated in patients with DM, while Wang et al found a strong association between skin AF and FMD in uremic patients on hemodialysis 10 ) .…”
Section: Introduction/aimmentioning
confidence: 99%
“…The flowchart of this systematic review and meta-analysis is presented in Figure 1 . The search retrieved a total of 90 articles, of which 25 studies [ 12 , 13 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] were selected for inclusion in the systematic review according to the inclusion criteria. Finally, 12 studies evaluating the association between PWv and SAF and 17 studies evaluating the association between C-IMT and SAF were identified and considered in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The study emphasized the role of skin AF as a predictor in the progression of DN. In view of type 2 diabetic patients, a recent study also confirmed that skin AF also significantly increased with the severity of DN [18].…”
Section: Skin Af As a Long-term Marker Of Dn Progressionmentioning
confidence: 75%